Optimizing cell‐free protein expression in CHO: Assessing small molecule mass transfer effects in various reactor configurations. Issue 7 (18th April 2017) - Peñalber‐Johnstone, Chariz; Ge, Xudong; Tran, Kevin; Selock, Nicholas; Sardesai, Neha; Gurramkonda, Chandrasekhar; Pilli, Manohar; Tolosa, Michael; Tolosa, Leah; Kostov, Yordan; Frey, Douglas D.; Rao, Govind
ABSTRACT: Cell‐free protein synthesis (CFPS) is an ideal platform for rapid and convenient protein production. However, bioreactor design remains a critical consideration in optimizing protein expression. Using turbo green fluorescent protein (tGFP) as a model, we tracked small molecule components in a Chinese Hamster Ovary (CHO) CFPS system to optimize protein production. Here, three bioreactors in continuous‐exchange cell‐free (CECF) format were characterized. A GFP optical sensor was built to monitor the product in real‐time. Mass transfer of important substrate and by‐product components such as nucleoside triphosphates (NTPs), creatine, and inorganic phosphate (Pi) across a 10‐kDa MWCO cellulose membrane was calculated. The highest efficiency measured by tGFP yields were found in a microdialysis device configuration; while a negative effect on yield was observed due to limited mass transfer of NTPs in a dialysis cup configuration. In 24‐well plate high‐throughput CECF format, addition of up to 40 mM creatine phosphate in the system increased yields by up to ∼60% relative to controls. Direct ATP addition, as opposed to creatine phosphate addition, negatively affected the expression. Pi addition of up to 30 mM to the expression significantly reduced yields by over ∼40% relative to controls. Overall, data presented in this report serves as a valuable reference to optimize the CHO CFPS system for next‐generation bioprocessing. Biotechnol. Bioeng. 2017;114: 1478–1486. © 2017 Wiley Periodicals, Inc. Abstract : By tracking the concentration of small molecule components such as nucleoside triphosphates, creatine, and inorganic phosphate in a CHO‐based cell‐free protein expression system, efficiency of mass transfer across a regenerated cellulose membrane in various off‐the‐shelf bioreactor devices was calculated. Results were directly correlated to yield, which provides a critical reference in the development of efficient strategies in bioreactor design to support the demonstrated potential of CHO‐based platforms for next‐generation bioprocessing.